2021
DOI: 10.1016/j.psj.2021.101463
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of different zinc sources to low-CP diets and its effect on performance, carcass traits, liver and kidney functions, immunological, and antioxidant parameters of quail chicks

Abstract: The present study was performed to evaluate the influence of low crude protein ( CP ) levels, zinc sources (organic as zinc methionine-Zn-Met and inorganic as zinc oxide-ZnO) and their interactions on growth performance, carcass traits, and blood components of growing Japanese quail. A total of 450 one-wk-old Japanese quail with the same body weights were randomly distributed into 9 groups of 50 birds. The 9-diet treatments comprised 3 levels of CP (20, 22, and 24%) and 3 Zn source (0 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…In this study, the growth performance reached the control level (CP, 18.55%) when supplementing the major AA pattern and all AA patterns in the low-protein diets (CP, 15.55%) in the goslings. Similar results were observed in low-protein diets in chickens ( Bezerra et al, 2016 ; van Harn et al, 2019 ; Teng et al, 2021 ), laying hens ( Alagawany et al, 2020 ; Uyanga et al, 2022 ), ducks ( Xie et al, 2017 ; Jiang et al, 2018 ), quail chicks ( Elsayed et al, 2021 ), and goose ( Wang et al, 2020 ). It is concluded that the growth performance would not be adversely affected by low-protein diets when the appropriate amount of AA is supplemented.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, the growth performance reached the control level (CP, 18.55%) when supplementing the major AA pattern and all AA patterns in the low-protein diets (CP, 15.55%) in the goslings. Similar results were observed in low-protein diets in chickens ( Bezerra et al, 2016 ; van Harn et al, 2019 ; Teng et al, 2021 ), laying hens ( Alagawany et al, 2020 ; Uyanga et al, 2022 ), ducks ( Xie et al, 2017 ; Jiang et al, 2018 ), quail chicks ( Elsayed et al, 2021 ), and goose ( Wang et al, 2020 ). It is concluded that the growth performance would not be adversely affected by low-protein diets when the appropriate amount of AA is supplemented.…”
Section: Discussionsupporting
confidence: 77%
“…In agreement with the results of the present study, De Grande et al [ 29 ] reported that there was no significant difference among the feed intake or bodyweight of the broilers which were fed different sources of zinc. Elsayed et al [ 30 ] evaluated the effect of different zinc sources (inorganic vs. organic) in low crude protein diets on the performance of quail chicks. The researchers found that the feed intake and the feed conversion ratio of the birds were not different among different experimental groups.…”
Section: Resultsmentioning
confidence: 99%
“…Slaughter performance, including dressed yield (%), half-eviscerated yield (%), eviscerated yield (%), breast muscle yield (%), leg muscle yield (%), and sum of breast and leg muscle yield (%), was measured and calculated according to the poultry production performance terms and metric statistics method 58 . Dressed weight is the weight of poultry after bloodletting, removal of feathers, foot cuticle, toe shell and beak shell.…”
Section: Methodsmentioning
confidence: 99%